Nanoinstabilities of Cu2O porous nanostructured films as driven by nanocurvature effect and thermal activation effect. (29th May 2019) - Zhu, Yiqi; Ma, Ji; Su, Jiangbin; Zhou, Lei; Jiang, Meiping; Zhu, Xianfang
Abstract: In this work, the instabilities at the nanoscale (i.e. nanoinstabilities) of triangular pyramids-like Cu2 O porous nanostructured films (PNFs) are studied by heating treatments under different atmosphere and temperature. It is found that the nanoscale building triangular pyramids turn round preferentially at the sharp angles and/or coalesce with their contacting ones by directional diffusion and plastic flow of atoms, which are driven by the nonuniformly-distributed surface nanocurvature. As a result, the triangular pyramids become quasi-sphere shape and the PNF evolves into a big, dense particles film. It is also observed that the heating or thermal activation effect efficiently promotes the reduction or oxidation of Cu2 O pyramids and the crystallization or growth of the as-achieved Cu or CuO grains. The above physical and chemical instabilities or changes at the nanoscale of Cu2 O PNFs can be well accounted for by the combined mechanism of nanocurvature effect and thermal activation effect. The nanocurvature effect can lower the energy barrier for the atom diffusion or plastic flow and lower the activation energy for the chemical reactions, while the thermal activation effect can supply the required kinetic energy or activation energy and make the atomic transportations and reactions kinetically possible. The findings reveal the evolution laws of morphology, crystal structure and composition of triangular pyramids-like Cu2 O PNF during heating treatments, which can further be extended to other types of Cu2 O PNFs. Also, the findings have important implications for the nanoinstabilities of Cu2 O PNFs-based devices, especially those working at a high temperature.